TANTANGAN KEPALA SEKOLAH/MADRASAH DALAM MENGIMPLEMENTASIKAN KURIKULUM BERBASIS CINTA DI MAN 1 OKU Selatan - Farah Hasanah Noor; Ahmad Zainuri; Muslim Gani Yasir (STKIP Subang, 2026)
This study aims to identify and analyze the challenges faced by the school/madrasah principal in implementing the Love-Based Curriculum (Kurikulum Berbasis Cinta/KBC) at MAN 1 OKU Selatan. KBC is an educational approach that places compassion (rahmah) as the primary foundation of the learning process, in alignment with Islamic educational values that emphasize the formation of noble character. This study employed a descriptive qualitative method with a case study design. Data were collected through in-depth interviews with the principal of MAN 1 OKU Selatan, non-participatory observation, and document analysis. Data analysis used the interactive model by Miles, Huberman, and Saldana (2014). The findings indicate that KBC implementation at MAN 1 OKU Selatan has proceeded on a solid conceptual foundation, supported by the transformational leadership of the principal. However, four main dimensions of challenges were identified: (1) resistance and uneven understanding among educators regarding the KBC paradigm; (2) limitations in facilities, infrastructure, and funding; (3) the diversity of student backgrounds requiring a differentiated approach; and (4) administrative burdens that diminish time available for pedagogical leadership. This study recommends strengthening teacher professional development programs, optimizing institutional partnership networks, and utilizing information technology in school administrative management.